Case-based Method and its Implementation in English for Medical Purposes - Laely Hidayati (Juliet, 2021)
Abstract The case study or case-based technique has been widely employed in a variety of areas due to the tremendous benefits it provides for teaching and learning. The Indonesian government also encourages the use of the case method as one of the methods emphasized in the Key Performance Indicators of Higher Education (IKU) guidelines. This article presents a literature review of the case study by exploring the benefits and the challenges of implementing this method in the classroom. Besides, an alternative scenario of the case study implementation in English for Medical Purposes is also presented. It is hoped that this article will give insight into the implementation of the case method in a specific setting to help students learn English in a meaningful way. Keywords: Key Performance Indicator, Case-based Learning, English for Medical Purposes